Penerapan Quality Function Deployment(QFD) Untuk Mengembangkan Kualitas Pelayanan Rawat Jalan Berorientasi Pelanggan Di Rumah Sakit Paru-Paru - Rudy Joegijantoro (LPPMK STIKES Widyagama Husada, 2012)
Quality Function Deployment (QFD) is defined as a method that supports the structured design of products or services. The method is based on the customer needs and involves all the relevant parties within an organization that develops and produces a product through teamwork. It is a method for mapping and prioritizing customer requirements into functional features and technical modules to optimize market performance. Although the quality of a service can be dramatically improved through a QFD exercise, the traditional crisp scoring approach has a major drawback. A wrong conclusion can be easily produced since the fuzzy nature of linguistic correlation terms from evaluation members is ignored. To overcome this problem, fuzzy scoring for linguistic terms is proposed in this paper. This study integrates fuzzy logic into House Of Quality to establish a framework for prioritizing customer requirements to simply, objectively, and scientifically analyze service features.